2009
DOI: 10.1111/j.1755-0238.2008.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-bloom leaf removal on growth of berry tissues and must composition in two redVitis viniferaL. cultivars

Abstract: Background and Aims:  Little work has been conducted on the effects that summer pruning operations have on the relative growth of grapevine berry parts. Our paper studies whether pre‐bloom leaf removal is able to modify the proportions of seed, skin and flesh in ripe grapevines berries and the related effects on must composition. Methods and Results:  Pre‐bloom defoliation (D) of the first six basal leaves on main shoots was applied to the field‐grown cvs Barbera and Lambrusco salamino (Vitis vinifera L.) in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
78
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 29 publications
14
78
0
5
Order By: Relevance
“…However, this theoretical model is, obviously, based on the assumption that the skin weight per unit area remains constant independently from berry size. From our data it is evident that, similarly to what can be found in literature Walker et al, 2005, Poni et al, 2009, changes in skin:berry weight ratio in relation to berry size are low (<1%). This lack of change in skin:berry weight ratio might be ascribed to the increase in skin weight per unit area (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…However, this theoretical model is, obviously, based on the assumption that the skin weight per unit area remains constant independently from berry size. From our data it is evident that, similarly to what can be found in literature Walker et al, 2005, Poni et al, 2009, changes in skin:berry weight ratio in relation to berry size are low (<1%). This lack of change in skin:berry weight ratio might be ascribed to the increase in skin weight per unit area (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…This is a consequence of the differential effect in carbohydrate metabolism in the grapevine. In addition to the intensity of leaf removal, the time period and frequency with which it is carried out, the cultivar, rootstock used, production period in tropical climates, vine training system, spacing between plants and rows, and the reserves available in the roots also determine the responses (Intrieri et al, 2008;Poni et al, 2008;Poni et al, 2009;Lee and Skinkis, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that different leaf removal methods, including both manual and mechanized, changed the canopy structure, leaf density, and the percentage of leaves and clusters, but did not affect bud fertility, shoot density, nor plant vigor (Percival et al, 1994). Early leaf removal carried out near flowering reduces the supply of carbohydrates to the fruit set/berry development and increases the leaf/fruit and skin/pulp ratios, resulting in less compact clusters which are less susceptible to disease, resulting in improved fruit composition and fewer thinned clusters (Poni et al, 2006;Poni et al, 2008;Poni et al, 2009;Intrieri et al, 2008;Austin et al, 2011). The time of leaf removal and shoot topping may affect fruit composition (Lee and Skinkis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Removing the leaves from cluster zone increases the evaporative potential within the fruit zone, lowering the humidity and making the cluster microclimate less conducive for the development of fungal diseases [11]. In the Sangiovese variety, characterized by highly compact clusters, early defoliation significantly reduced the fruit set, yield per shoot, cluster weight, number of berries per cluster, and cluster compactness [6,7,12]. Autochtonous variety, Vranac is also characterized by highly compacted clusters; we decided to apply these agro-techniques in order to reduce the yield parameters hoping that it would have the same beneficial effects as in the case of Sangiovese variety.…”
Section: Introductionmentioning
confidence: 99%